2020
DOI: 10.1021/acs.energyfuels.9b04191
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylsulfonamides as Kinetic Hydrate Inhibitors

Abstract: Kinetic hydrate inhibitor (KHI) polymers have been used for over 25 years to prevent gas hydrate formation in oil and gas production flow lines. KHI polymers are water-soluble at hydrate formation conditions, and most of them contain amide (−NH–C­(O)−) functional groups. The water solubility is due to their strong hydrophilicity and hydrogen-bonding ability. In this report, we have investigated various classes of polyvinylsulfonamides as KHIs for the first time. The carbonyl moiety in the amide group can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The presence of salt fragments and PEG residue contributes to an increase in the solubility of polyurethanes in an aqueous medium and facilitates an additional interaction with water molecules through hydrogen bonds disturbing the local water structuring. This is one of the key factors in kinetic gas hydrates inhibition [36,37]. In addition, two more advantages of the developed inhibitors should be noted.…”
Section: Chemistrymentioning
confidence: 99%
“…The presence of salt fragments and PEG residue contributes to an increase in the solubility of polyurethanes in an aqueous medium and facilitates an additional interaction with water molecules through hydrogen bonds disturbing the local water structuring. This is one of the key factors in kinetic gas hydrates inhibition [36,37]. In addition, two more advantages of the developed inhibitors should be noted.…”
Section: Chemistrymentioning
confidence: 99%
“…Recently, we have explored polymers without amide groups as KHIs and shown that some polymer classes can give reasonable performance, albeit not as powerful as the best amide-based polymers. We have also investigated maleic-based amide polymers as KHIs since the monomer maleic anhydride (MA) is a cheap raw material. Maleic-based KHI polymers have been known since the 1990s, but recent advances in structure–activity analysis have led to polymers with improved performance. , For example, the vinyl acetate/MA copolymer in which the anhydride is reacted with a 60:40 mixture of cyclohexylamine/3-di- n -butylaminopropylamine [VA:MA-60%cHex-40%DBAPA, M n = 11 kg/mol, 25 wt % in 2-butoxyethanol (nBGE)] gave a significantly better performance than previously reported maleamide polymers (also in nBGE) or PVCap (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…This SNG composition is given in Table . We used our standard slow constant-cooling (SCC) test method, which we have used in many previous studies with this equipment. This allows the reader to compare the results to many other classes of additives tested in our laboratories. A study recently showed that the slow ramped cooling experiments gave good reproducibility and recommended lowering the temperature by 0.5 °C every 3 h .…”
Section: Methodsmentioning
confidence: 99%